PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI TERHADAP KINERJA PEGAWAI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI SUMATERA UTARA - Yoga Simatupang; Ferry Panjaitan; Romindo M Pasaribu; Orlando Steven (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to determine the effect of career development and motivation on employee performance at the Office of the Human Resources Development Agency of North Sumatra Province. The sampling technique is carried out using non-probability sampling with saturated sampling techniques. The sample of this study was taken as many as 76 respondents. The data collection technique is carried out by distributing direct questionnaires. The data analysis technique used in this study is quantitative. Based on research that has been conducted using multiple linear regression analysis, namely Y = 2.190 + 0.393X1 + 0.469X2 +e which shows that career development and motivation variables have a positive and significant effect on employee performance at the Office of the Human Resources Development Agency of North Sumatra Province. The results of the partial test (t-test) were obtained from the results of the assessment of career development variables that had a positive and significant effect on employee performance at the Office of the Human Resources Development Agency of North Sumatra Province. The results of the F test of career development and motivation variables simultaneously have a positive and significant effect on employee performance at the Office of the Human Resources Development Agency of North Sumatra Province.And the results of the coefficient of determination (R2) test of career development and motivation variables can explain employee performance at the Office of the Human Resources Development Agency of North Sumatra Province by 0.802 or 80.2%, the remaining 19.8% is explained by other variables that are not studied in this study